Digital Bank Transformation: Sustainable Innovation in Financial Institutions - Sendjaja, Theodorus; Rivai Zainal, Veithzal; Sofriana Imaningsih, Erna; Christina Nawangsari, Lenny; Johanes Lo, Singmin (Riviera Publishing, 2022)
Introduction: Bank digital transformation is a continuous innovation from conventional commercial banks to digital banks. The driving force in traditional retail banks to carry out sustainable innovation can be seen from the internal and external sides in the form of mutually supportive operations and strategies. In the face of competitive pressures, businesses in the financial services industry increasingly depend on innovation and sustainability to succeed and survive. The stress of business competition has made many banks worldwide close their branch offices in recent years. Method: This study is a literature study that collects theoretical references relevant to sustainable innovation in financial institutions, focusing on two main topics: sustainable digital technology innovation in Fintech and banks' digital transformation. Result: Fintech uses digital technology as a sustainable solution in offering financial inclusion services that are difficult for old players in the financial industry to fulfill. Fintech appears in peer-to-peer lending, virtual marketplaces and digital currencies. For the Bank's digital transformation, several regulations from the Financial Services Authority related to sustainable innovation must be complied with. Financial Services Authority Regulation Number 51/POJK.03/2017 concerning implementing Sustainable Finance for Financial Services Institutions, Issuers and Public Companies. Financial Services Authority Regulation Number 13/POJK.02/2018 concerning Digital Financial Innovation in the Financial Services Sector. Conclusion: The driving force in the Company to carry out sustainable innovation can be seen from the internal and external sides in the form of mutually supportive operations and strategies. The proposed digital transformation strategy for the Bank's continuous innovation is as follows: compliance with regulators, customer-centric, openness principles, and making digital a core value in business.